PENGEMBANGAN KURIKULUM DI INDONESIA MENGHADAPI TUNTUTAN KOMPETENSI ABAD 21 - Budi Agus Sumantri (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
Abstract: Curriculum Development in Indonesia Facing 21st Century Demands. This study aims to describe curriculum development in Indonesia in facing the challenges of 21st century competence. This research method uses library research to be analyzed and witnessed. Research data is obtained from the results of records from books and journals. The steps to procuring data include: (1) a global perspective in curriculum development, (2) teacher roles and challenges, (3) curriculum development in Indonesia. The results of this study contain global perspectives in curriculum development: (1) 21st century learning activities, (2) characteristics of 21st century learning. Related to teacher roles and challenges include: (1) teacher's role in the 21st century, (2) 21st century teacher competency And curriculum development in Indonesia, as follows: (1) Curriculum development in Indonesia faces the challenges of 21st century competencies, (2) 21st century learning models. The conclusion of this study is that the curriculum that has a global perspective is not only national or local. This curriculum must be able to bring students to global thinking in the sense that students are able to disclose information and maybe this can be used as a display that helps them become productive citizens. The skills needed in the 21st century include: 1) innovation innovation skills, 2) information skills, median and technology, 3) life and career skills.Abstract: Pengembangan Kurikulum di Indonesia Menghadapi Tuntutan Abad 21. Penelitian ini bertujuan untuk mendeskripsikan tentang pengembangan kurikulum di Indonesia dalam mengahadapi tuntutan kompetensi abad 21. Metode penelitian ini adalah menggunakan penelitian kepustakaan yang akan dianalisis dan disimpulkan. Data penelitian diperoleh dari hasil pencatatan dari buku dan jurnal. Langkah-langkah pengadaan data meliputi: (1) perspektif gelobal dalam pengembangan kurikulum, (2) peran dan tantangan guru, (3) pengembangan kurikulum di indenesia. Hasil penelitian ini berupa perspektif gelobal dalam pengembangan kurikulum: (1) aktivitas pembelajaran abad 21, (2) karakteristik pembelajaran abad 21. Adapun untuk peran dan tantangan guru meliputi: (1) peran guru pada abad 21, (2) kompetensi guru abad 21. Dan pengembangan kurikulum di Indonesia, sebagai berikut: (1) pengembangan Kurikulum di Indonesia mengahadapi tuntutan kompetensi abad 21, (2) model pembelajaran abad 21. Kesimpulan dari penelitian ini, kurikulum yang bercorak perspektfi global adalah kurikulum yang juga memuat wawasan global, bukan hanya nasional ataupun lokal. Kurikulum tersebut harus mampu membawa siswa untuk berpikir global dalam arti siswa mampu mengungkapkan informasi sebanyak mungkin dan informasi tersebut dapat digunakan sebagai pajangan yang mengarahkan mereka menjadi warga negara yang produktif. Adapun keterampilam yang dibutuhkan pada abad 21meliputi: 1) learning innovation skill, 2) information, median and technology skill, 3) life and carrer skill.